Questionnaire testing, validating, and preliminary results - Marco Antonio ORTIZ SANCHEZ; Philomena M. Bluyssen (A+BE: Architecture and the Built Environment, 2019)
Abstract This paper demonstrates the effectiveness of the TwoStep cluster analysis and the development and first results of a new questionnaire for measuring comfort, health, and energy habits. The justification for the questionnaire is to consolidate questions of six specific domains about occupants' energy consumption patterns, from the behavioural and psychological perspectives into one instrument. The questionnaire was developed from a literature review, iterative conceptualization, and testing. The resulting instrument was administered to a sample of home occupants, comprising of bachelor students of Architecture of the Delft University of Technology. The objective of the study was to examine the effectiveness of the TwoStep cluster analysis to produce occupant profiles. 316 emails were sent out inviting participants to complete the questionnaire. With the TwoStep cluster analysis, it was possible to distinguish six different archetypes of occupants based on their behavioural characteristics. These were the Relaxed Optimists, Unconcerned Indifferents, Restrained Sensitives, Positive Absolutists, Incautious Negativistics, and Resigned Savers. The results provide promising evidence of the questionnaire's potential to distinguish different occupant energy-consumption profiles based on distinct psychosocial domains in a single and concise instrument, while also showing that the analysis method is appropriate for the type of variables gathered. The value of recognizing these profiles allows for a better understanding of occupants' differing energy consumption patterns in their homes and tailoring interventions to their specific needs.